A Histopathological spectrum of nephrectomy specimens in a tertiary hospital of Raipur city (C.G.) India - Ajay Singh Thakur; Renuka Gahine; Bimla Banjare (Tropical Journal of Pathology and Microbiology, 2019)
Introduction- Kidneys are one of the major organs of the human body that serve several essential functions. Their main function is to regulate the balance of electrolytes in the blood, along with maintaining pH homeostasis. Kidneys are affected by various non-neoplastic and neoplastic pathological processes. Kidneys with end stage renal disease can give rise to major complications such as massive bleeding for which nephrectomy may be indicated. Radical or partial nephrectomy is the treatment of choice for a great proportion of patients with renal tumors.Materials and Methods- Thiswas a retrospective study carried out in the Department of Pathology in Pt. J. N. M. Medical College Raipur, Chhattisgarh, India. A total of54 nephrectomy specimens received during the period were included in the study. Paraffin blocks and slides along with case records were retrieved and studied.Results- Patients with a male to female ratio of 1.3:1. Maximum cases of chronic pyelonephritis were seen in the age group of 31-40 years. Among 54 nephrectomy cases, 16(29.6%) cases were non-neoplastic lesions and 38 (70.4%) of the cases were neoplastic lesions. Among 20 cases of renal cell carcinoma, clear cell renal carcinoma 9 (45%) cases was the most frequent followed by papillary RCC 7 (30%) cases. Other tumors included 2 (10%) cases of unclassified RCC, one (05%) case each of chromophobe RCC, medullary RCC and collecting duct RCC.Conclusion- A wide histopathological range of lesions comprised of neoplastic and non-neoplastic lesions was found. Increase in availability of early diagnosis and appropriate better treatment facilities causes decrease in need of surgical treatment for inflammatory lesions of kidney.